The makeshift curtain: A generous Christianity: Ecclesiologies beyond the religious‐secular binary. Issue 2 (13th June 2021) - Wyller, Trygve
Abstract: The article discusses how one might reflect further on ecclesiological impacts from Scandinavian creation theology (SCT). The idea is that the SCT from Gustaf Wingren and Knud Ejler Løgstrup opens for an ecclesiology beyond the secular‐religious binary. A generous Christianity appears when practices of non‐faith (secularity) take place within ecclesia. The article discusses a concrete case from the Swedish congregation Bergsjøen where a makeshift curtain for visiting Muslims is constructed in the church basement. The makeshift curtain could be interpreted as a representation of creation and in this way being an important part of the ministry as a whole. The article discusses with recent Nordic and international ecclesiological and political theology. The conclusion is that, different from Catherine Keller's proposal of a "weak" political theology, SCT opens for an embodied, generous, Christianity.